1982
DOI: 10.1111/j.1755-3768.1982.tb08381.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression Analysis of the Central Visual Field in Chronic Glaucoma Cases

Abstract: KRAKAU90 glaucoma cases (160 eyes) with field defects in at least one eye have been subjected to automatic perimetry on at least 5 occasions. The condition of the fields is summarized in single numbers. Regression analysis has been applied to series of such performance numbers. The trend of the development of the field defect is represented by the regression coefficient. The frequency distribution of the coefficients in groups based on references to age, sex, intraocular pressure, exfoliations, haemorrhages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 3 publications
2
46
0
Order By: Relevance
“…Unlike event detection, assessment of this “rate of progression” should permit the prediction of blindness occurring during lifetime and thus provide information on the need for treatment or its intensification 2. They emphasised the need for frequent perimetry in glaucoma and ended with recommending six fields in the first 2 years.…”
mentioning
confidence: 99%
“…Unlike event detection, assessment of this “rate of progression” should permit the prediction of blindness occurring during lifetime and thus provide information on the need for treatment or its intensification 2. They emphasised the need for frequent perimetry in glaucoma and ended with recommending six fields in the first 2 years.…”
mentioning
confidence: 99%
“…4 Correlogram of visual field test locations from a group of stable glaucoma eyes. As the distance between visual field test points decreases, the correlation among them tends to increase exponentially 1) Holmin and Krakau first drew attention to the fact that a minimum of 6-8 measurements are required before a meaningful regression analysis can be performed on visual field data [53,54]. Therefore, multiple exams, which may require a long period of follow-up, are required before linear regression analysis can be effectively used.…”
Section: Regional Trend Analysesmentioning
confidence: 98%
“…This was because our preliminary study and previous reports (Holmin, 1982;Katz, 1997;Spry, 2000; showed that at least 5 or 6 sets of examination test results were necessary for exact trend-type analysis. No reliable, unexpected, or unreasonable results were excluded.…”
Section: Patient Selectionmentioning
confidence: 99%
“…While trend-type analysis is more statistically reliable than event-type analysis, it requires longer follow-up periods and more test results. Some investigations have confirmed that trend-type analysis ideally requires 6 to 7 or more test results (Holmin & Krakau, 1982;Katz et al, 1997;Spry et al, 2000;. Thus, for this type of analysis they recommended performing at least 3 visual field examinations within 2 to 3 years from the start of follow-up .…”
mentioning
confidence: 99%